Rethinking CIGS solar cells for rear illumination applications - Léo Choubrac; Fabien Pineau; Eugène Bertin; Ludovic Arzel; Nicolas Barreau (JPhys Energy)
This study introduces a chalcogenide-based thin-film solar cell structure optimized for rear illumination, featuring a thinner, wide-bandgap Cu(In,Ga)S _2 chalcopyrite absorber. Matching the performance of traditional front-illuminated designs, this configuration paves the way for further photoelectrochemical advances thanks to its metallic top layer, which can serve as a versatile grafting platform that is resistant to their operating conditions.